Dosimetry verification of three‐dimensional printed polylactic acid template‐guided precision 125I seed implantation for lung cancer using a desktop three‐dimensional printer. Issue 10 (6th September 2021) - Han, Xiaoyan; Fang, Shu; Sheng, Rui; Wang, Yi; Zhou, Jinhua; Wang, Jiong
Abstract: Introduction: The purpose of this study was to verify the effectiveness of polylactic acid (PLA) template puncture route planning by comparing preoperative and postoperative dosimetry using computerized tomography (CT)‐guided implantation of 125 I radioactive seeds. Methods: A total of 28 patients who underwent 125 I seed implantation between January 2018 and June 2019 were selected for the statistical study of seed dosimetry. All patients received preoperative treatment planning system (TPS) planning, of which 13 patients in the experimental 3D template group underwent intraoperative puncture and implantation using the PLA template planning route. The other 15 patients in the traditional control group underwent intraoperative puncture and implantation using CT images for guidance. By calculating the dose‐volume histogram, preoperative and postoperative D90 values and postoperative V90 values were compared between the two groups. Results: The mean D90 values in the template group before and after surgery were 136.06 ± 7.10 and 134.72 ± 7.85 Gy, respectively. There was no statistically significant difference. The preoperative and postoperative mean D90 values in the traditional group were 132.97 ± 8.04 and 126.06 ± 9.19 Gy, respectively, which were statistically significantly different. The mean postoperative V90 values in the template and traditional groups were 93.80 ± 1.34% and 88.42 ± 6.55 %, respectively, showing a statistically significant difference. Conclusions: The preoperative TPS plan for the experimental group guided by the PLA template was almost the same as that for the final guided particle implantation. The dose parameters in the experimental group were also better than those in the traditional group, making the use of the presented PLA template more efficient for clinical applications.